The Use of Gamelan in Pancasila Learning to Cultivate a Sense of Love for the Homeland in Elementary School Students - Koestanti, Jeny; Maulida, Dinda Laurenza Nailis Sikhah; Wijayanto, Wasis (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: This study aims to foster a sense of love for the homeland of students in learning Pancasila education national compulsory songs through saron media in order to increase student interest in learning at SD 4 Kandangmas Kudus. Research Methods: As for this research using an approach with qualitative methods with phenomenological design, by involving fifth grade students in singing national songs accompanied by gamelan saron musical instruments. Finding/Results: The results of this study show that the integration of gamelan saron in learning not only increases students' interest and participation, but can also deepen their understanding of national values. Despite the challenges in introducing the saron musical instrument, this approach proved effective in shaping the character of discipline and nationalism. Conclusion: This study emphasizes the importance of innovation in learning methods that connect culture with education to strengthen national identity from an early age.